DETERMINANTS OF GENERATION Z’S INTEREST IN CHOOSING A CAREER IN THE FORMAL SECTOR (A Study in Denpasar City) - Adrian Maulana; Ni Putu Martini Dewi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The formal sector is an important pillar of national economic stability as it offers a structured work system, legal certainty, and social protection. However, in the digital era, the career preferences of young generations have begun to shift, creating an urgency to understand the reasons why Generation Z continues to consider the formal sector amid the rapid growth of informal sector employment. This study aims to analyze the determinants of Generation Z’s interest in Denpasar City in choosing a career in the formal sector by examining the effect of education level (X1), socioeconomic status (X2), and income (X3). The urgency of this study lies in the importance of mapping young labor force expectations to support more effective and sustainable employment absorption policies. This study employs a quantitative approach with data collected through questionnaires from 100 Generation Z respondents in Denpasar City using a purposive sampling technique. The data analysis method used is multiple linear regression analysis to test the effect of variables partially and simultaneously. The results show that simultaneously, education level, socioeconomic status, and income have a significant effect on Generation Z’s interest in choosing a career in the formal sector. Partially, all three variables also have a positive and significant effect. Income is the most dominant factor, emphasizing that financial security is the primary motivator for Generation Z, which is known for being realistic in future planning. These findings imply that academic qualifications and financial expectations constitute Generation Z’s strategic foundation in choosing a professional career path. The government must ensure equitable access to formal employment through inclusive policies.